2023
DOI: 10.3390/nu15040832
|View full text |Cite
|
Sign up to set email alerts
|

Re-Visiting Antioxidant Therapy in Murine Advanced Atherosclerosis with Brussels Chicory, a Typical Vegetable in Mediterranean Diets

Abstract: Brussels chicory, a typical vegetable in Mediterranean diets, has been recently reported to stabilize advanced atherosclerotic plaques in the brachiocephalic artery of apoE-deficient (Apoe−/−) mice. Herein, we investigated whether Brussels chicory can stabilize advanced plaques in the aorta via improving oxidative stress. Thirty week old Apoe−/− mice were fed the AIN-93G diet or supplemented with 0.5% freeze-dried Brussels chicory for twenty weeks. Aortic plaque size and stability, aortic relaxation, monocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The results showed that the administration of chicory could improve oxidative stress and promote the protection of chicory against atherosclerosis. 112,113…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…The results showed that the administration of chicory could improve oxidative stress and promote the protection of chicory against atherosclerosis. 112,113…”
Section: Pharmacological Activitymentioning
confidence: 99%